Organizational Change and Management - Maes, Guido; Van Hootegem, Geert (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Since Kurt Lewin (1947) first published his article Frontiers in Group Dynamics 75 years ago, countless publications in the form of articles and books have been written on the topic of organizational change. There remains a great deal to be discussed and deliberated about organizational change. The articles in this Special Issue have been carefully selected to provide new insights into the vast domain of organizational change.